Understanding the functions and operations of data monitoring committees: Survey and focus group findings. (February 2017) - Calis, Karim A; Archdeacon, Patrick; Bain, Raymond P; Forrest, Annemarie; Perlmutter, Jane; DeMets, David L
Background: The use of data monitoring committees in the conduct of clinical trials has increased and evolved, but there is a lack of published information on when data monitoring committees are needed and utilized, the acceptable range of data monitoring committee practices, and appropriate qualifications of data monitoring committee members. Methods: To gain a better understanding of data monitoring committee operations and areas for improvement, the Clinical Trials Transformation Initiative conducted a survey and set of focus groups. A total of 143 respondents completed the online survey: 76 data monitoring committee members, 52 sponsors involved with organization of data monitoring committees, and 15 statistical data analysis center representatives. There were 42 focus group participants, including data monitoring committee members; patients and/or patient advocate data monitoring committee members; institutional review board and US Food and Drug Administration representatives; industry, government, and non-profit sponsors; and statistical data analysis center representatives. Results: Participants indicated that the primary responsibility of a data monitoring committee is to be an independent advisory body representing the interests of trial participants by assessing the risk and benefit ratio in ongoing trials. They noted that data monitoring committees must have access to unmasked data in order to perform this role. No clear consensus emerged regarding specific criteria for requiring a data monitoring committee for a given trial, and some participants felt data monitoring committees may be overused. Respondents offered suggestions for the data monitoring committee charter and communications with sponsors, institutional review boards, and regulators. Overall, data monitoring committee members reported that they are able to function independently and their recommendations are almost always accepted by the sponsor. Participants indicated that there are no standards or guidelines pertaining to qualifications of data monitoring committee members. Furthermore, only 8% (6/72) of data monitoring committee member survey respondents received any formal training, and 94% (68/72) were not aware of any training programs. Conclusion: Findings from the survey and focus groups provide a better understanding of contemporary data monitoring committee operations and insights regarding challenges and best practices. Overall, it was clear that increased training will be needed to prepare the next generation of qualified data monitoring committee members to meet the growing demand. These findings can be used by Clinical Trials Transformation Initiative and others to develop recommendations and tools to improve data monitoring committee operations and the overall quality of trial oversight.